Gastrointestinal Mastocytosis: A Potential Diagnostic Pitfall to Be Aware. (September 2019) - Zanelli, Magda; Pai, Rish K.; Grazia Zorzi, Maria; Zizzo, Maurizio; Martino, Giovanni; Morelli, Luca; Parisi, Alice; De Marco, Loredana; Annessi, Valerio; Ascani, Stefano
Mastocytosis is a rare and heterogeneous group of disorders that may be limited to the skin and even spontaneously regress or may have a systemic presentation with multi-organ involvement and poor outcome. Among the extracutaneous sites, gastrointestinal tract is often affected, but nonspecific clinical manifestations combined with subtle histological findings of the disease makes the diagnosis of gastrointestinal mastocytosis rather hard. In absence of a high index of suspicion, gastrointestinal involvement is easily overlooked. We report a challenging case of systemic mastocytosis presenting with isolated gastrointestinal manifestations without skin involvement, in which the diagnosis was missed at first evaluation of intestinal biopsies.